Implications for Provincial Economies of Meeting China's NDC through an Emission Trading Scheme : A Regional CGE Modeling Analysis - Pang, Jun; Timilsina, Govinda (World Bank, Washington, DC, 2019)
This study analyzes the potential impacts of a national emission trading scheme on provincial economies in China of meeting China's emission reduction pledges, the Nationally Determined Contributions announced under the Paris Agreement. The study developed a multiregional, multisectoral, recursive-dynamic computable general equilibrium model and calibrated it with the latest provincial-level social accounting matrices (2012). The study shows that meeting China's Nationally Determined Contributions through an emission trading scheme would reduce almost 30 percent of the emission reduction from the business as usual scenario in 2030. If the baseline is corrected based on information from a bottom-up energy sector model, TIMES, the required reduction of emissions from the baseline in 2030 drops by half, to 15 percent. At the national level, the emission trading scheme would cause a 1.2 to 1.5 percent reduction in gross domestic product from the business as usual scenario in 2030. If the baseline is corrected, the impact on gross domestic product drops by two-thirds. The emission trading scheme would cause some provincial economies to gain and others to lose. The economic impacts are highly sensitive to the allowance allocation rules. Not only the magnitudes, but also the directions of the economic impacts alter when the allocation rules change. The provinces that rely on coal mining or coal-intensive manufacturing industries are found to experience relatively larger economic losses irrespective of the allowance allocation rules.